Parametric amplification in coupled nonlinear waveguides: The role of coupling dispersion - Shi, Minji; Ribeiro, Vitor; Perego, Auro M. (Frontiers in Photonics, 2023)
We present the theory of parametric amplification in coupled nonlinear waveguides considering the frequency dependency of the coupling strength. We show that coupling dispersion can indeed compensate for the uncoupled individual waveguides dispersion enabling a substantial tailoring of the gain spectrum. Our theory describes both phase-sensitive and phase-insensitive operational modes, it can be straightforwardly generalized to include arbitrary higher-order waveguide and coupling dispersion and its predictions agree very well with numerical simulations both in the presence and in the absence of waveguide losses. It provides a tool for the design of novel versatile parametric amplifiers based both on coupled integrated waveguides and dual-core fibers too.